Danziger Wähler! (Gdańsk : [s.n.], 1933)
Druk zachęcający do głosowania na polską listę w wyborach do gdańskiego Volkstagu.
Keywords: Wybory -- Polska -- Gdańsk -- 1900-1945 -- druki ulotne; Partie polityczne -- Polska -- Gdańsk -- 1900-1945.; Gdańsk (Polska) -- 1920-1939 (Wolne Miasto) -- druki ulotne; Gdańsk (Polska) -- 1920-1939 (Wolne Miasto) -- źródła; Gdańsk (Polska) -- polityka i rządy -- 1900-1945.